SIKAP, HARAPAN, DAN PERSEPSI SISWA PADA MATEMATIKA SERTA IMPLIKASINYA TERHADAP KEMAMPUAN REGULASI DIRI - Kusaeri, Kusaeri; Cahyan, Ekky Dea Henwi (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2016)
In this study, we composed a theoretical model as well as empirically tested the relationship between attitude, expectation, and perception towards mathematics with studentsâ self-regulation ability. Studentsâ attitude, expectation, perception, and self-regulation ability data were collected from a questionnaire to 104 eight graders in one of public junior high schools in West Surabaya. The collected data were analyzed using Structural Equation Modeling (SEM) by Lisrel Software version 9.2 to determine relationship between the evaluated variables. Theoretical modeling showed that expectation and perception affected studentsâ self-regulation ability while attitude serves as an intervening variable. The contribution of each variable indicated a different degree of interconnection. Empirical testing suggested that attitude and perception directly affected studentsâ self-regulation ability, while expectation did not. The connection between expectation and perception with studentsâ attitude towards mathematics were affirmed in empirical testing results in which it clearly showed that expectation and perception contributed to studentsâ attitude towards mathematics.